TINJAUAN YURIDIS TERHADAP BUDAYA HUKUM PELAKSANAAN PENANDATANGANAN BLANKO AKTA JUAL BELI TANAH (Studi di Kabupaten Klaten) - Erick Augusta Irawan; Sapto Hermawan; Heri Hartanto (Media Bina Ilmiah, 2025)
This study examines the juridical review of the legal culture of the community in the implementation of land sale and purchase deed signing in Klaten Regency, taking into account the latest positive legal provisions, particularly Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units, and Land Registration, as well as Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 16 of 2021 concerning Procedures for the Registration of Transfer of Land Rights. The signing of the sale and purchase deed by the parties before the Land Deed Official (PPAT) is a legal requirement in the process of land rights transfer, providing legal certainty and protection. However, in practice in Klaten Regency, local legal cultural influences that do not fully support orderly land administration are still found, such as the tendency to conduct transactions without authentic deeds or the involvement of unofficial third parties. This study uses an empirical juridical method with a sociological approach, through document studies and interviews with the community, PPATs, and local BPN officials. The results show that low legal awareness and the strong influence of local customary practices are the main obstacles in the implementation of land sale and purchase according to regulations. Therefore, synergy between regulatory reform and educational approaches to the community is needed to foster a legal culture that complies with statutory regulations.